A comprehensive retrieval method of social media information based on fuzzy mathematics. (14th March 2023) - Yu, Xinyan
In order to solve the problems of low retrieval accuracy and long retrieval time of traditional information comprehensive retrieval methods, a social media information comprehensive retrieval method based on fuzzy mathematics is proposed in this paper. Firstly, the social media information data is collected by hash function; Then, the cross filter is used to remove similar social media data. Finally, according to the fuzzy triangle number in the fuzzy mathematics method, the keyword weight in social media information is calculated. The comprehensive retrieval of social media information is completed by determining the attribute of social media information and reducing the word frequency range of social media information. The experimental results show that the minimum detection error of this method is about 0.15%, and the shortest information retrieval time is about 1.0 s. The retrieval effect of the proposed method is good.